ESTABLISHING THE LINK BETWEEN THE CHESAPEAKE BAY IMPACT STRUCTURE AND THE NORTH AMERICAN TEKTITE STREWN FIELD: THE SR-ND ISOTOPIC EVIDENCE - Deutsch A.; Koeberl C. (My University, 2006)
The Chesapeake Bay impact structure, which is about 35 Ma old, has previously been proposed as the possible source crater of the North American tektites (NAT). Here we report major and trace element data as well as the first Sr-Nd isotope data for drill core and outcrop samples of target lithologies, crater fill breccias, and post-impact sediments of the Chesapeake Bay impact structure. The unconsolidated sediments, Cretaceous to middle Eocene in age, have εSrt=35.7Ma of +54 to +272, and εNdt=35.7Ma ranging from -6.5 to - 10.8; one sample from the granitic basement with a TNdCHUR model age of 1.36 Ga yielded an εSrt=35.7Ma of + 188 and an εNdt=35.7Ma of -5.7. The Exmore breccia (crater fill) can be explained as a mix of the measured target sediments and the granite, plus an as-yet undetermined component. The post-impact sediments of the Chickahominy formation have slightly higher TNdCHUR model ages of about 1.55 Ga, indicating a contribution of some older materials. Newly analyzed bediasites have the following isotope parameters: +104 to +119 (εSrt=35.7Ma), -5.7 (εNdt=35.7Ma), 0.47 Ga (TSsUR), and 1.15 Ga (TNdCHUR), which is in excellent agreement with previously published data for samples of the NAT strewn field. Target rocks with highly radiogenic Sr isotopic comparison, as required for explaining to isotopic characteristic of Deep Sea Drilling Project (DSDP) site 612 tektites, were not among the analyzed sample suite, Based on the new isotope data, we exclude any relation between the NA tektites and the Popigai impact crater, athough they have identical ages within 2σ errors. The Chesapeake Bay structure, however, is now clearly constrained as the source crater for the North American tektites, although the present data set obviously does not include all target lithologies that have contributed to the composition of the tektites. © The Meteoritical Society, 2006.
Keywords: Cretaceous; Eocene; Mesozoic::Cretaceous; Мезозой::Меловая; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен